2022
DOI: 10.1007/s10943-022-01721-3
|View full text |Cite
|
Sign up to set email alerts
|

(Un)holy Smokes? Religion and Traditional and E-Cigarette Use in the United States

Abstract: This study employed national cross-sectional survey data from the 2021 Crime, Health, and Politics Survey ( n = 1578 to 1735) to model traditional cigarette and e-cigarette use as a function of religious affiliation, general religiosity, biblical literalism, religious struggles, and the sense of divine control. Although the odds of abstaining from cigarettes and e-cigarettes were comparable for conservative Protestants and non-affiliates, conservative Protestants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
(206 reference statements)
0
2
0
Order By: Relevance
“…It is possible that perceived neighborhood disorder—and its visual and social cues—could contribute to spiritual struggles, which in turn to erode self-esteem. For example, the experience of neighborhood disorder could lead individuals to grapple in new ways with the idea that God has visited such chronic strains upon them, which could lead them to feel less worthwhile and competent as individuals (Hill et al 2023). As an alternative to this potential mediating pattern, it is possible that spiritual struggles could exacerbate the already problematic link between neighborhood disorder and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that perceived neighborhood disorder—and its visual and social cues—could contribute to spiritual struggles, which in turn to erode self-esteem. For example, the experience of neighborhood disorder could lead individuals to grapple in new ways with the idea that God has visited such chronic strains upon them, which could lead them to feel less worthwhile and competent as individuals (Hill et al 2023). As an alternative to this potential mediating pattern, it is possible that spiritual struggles could exacerbate the already problematic link between neighborhood disorder and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 25 years or so, empirical studies have linked perceived neighborhood disorder with an array of psychosocial and behavioral outcomes, including, for example, mistrust, social isolation, perceived powerlessness, religious and spiritual struggles, heavy drinking, sleep disturbance, psychological distress, and poor physical health (Blair et al 2014; Carbone 2020; Geis and Ross 1998; Hill, Burdette, and Hale 2009; Hill, Ross, and Angel 2005; Hill et al 2016, 2023; Intravia et al 2016; Johnson, Billings, and Hale 2018; Kim and Conley 2011; O’Brien, Farrell, and Welsh 2019; Ross and Jang 2000; Ross, Mirowsky, and Pribesh 2001; Ross and Mirowsky 2009). Studies have also reported inverse associations between perceived neighborhood disorder and self-esteem (Behnke et al 2011; Haney 2007; Hill et al 2013; McMahon, Felix, and Nagarajan 2011; Pederson et al 2022; Prelow et al 2006).…”
Section: Introductionmentioning
confidence: 99%